Analisis Kinerja Ekonomi Usaha Sapi Perah Di Kecamatan Baturadenkabupaten Banyumas - Aji, Gilang Perdana Wisnu; Mastuti, Sri; Hidayat, Nunung Noor (ANGON: Journal of Animal Science and Technology, 2019)
Background.This research was held on April 10th until June 1st, 2018 in Baturraden District, Banyumas Regency. The purpose of this research was 1). To know the economic performance (income and business efficiency) of dairy cattle business in Baturraden District, Banyumas Regency; 2). Analyze the factors (number of livestock ownership, feed costs, dairy farming experience, number of family members and education level of daily farmer) that affect the economic performance of dairy cattle business in Baturraden District, Banyumas Regency. Materials and methods. This research was conducted with survey method and the subject was dairy farmers in Baturraden Subdistrict, Banyumas Regency. The area sampling method was carried out with cluster sampling technique on 6 milk producing districts in Banyumas Regency and Baturraden District was selected as there was 20 dairy farmers as respondents. Income and business efficiency were analyzed by cash flow analysis, while the factors (number of livestock ownership, feed costs, dairy farming experience, number of family members and daily farmer education) that affecting economic performance (income and business efficiency) were analyzed using multiple linear regression. Results.The results show that 1). The average income of dairy cattle business in Baturaden Subdistrict was Rp. 35.557.684/year and the average business efficiency was 2.26; 2). The factors that significantly affecting the income are number of livestock ownership (P <0.10), feed costs (P <0.05) and daily farming experience (P <0.05). Feed costs partially have a significant effect on business efficiency (P <0.05). Dairy business in Baturraden District is profitable and runs efficiently. Conclusion.Conclusion: 1). Dairy cattle business in Baturraden Regency was quite profitabe dan efficient; 2). The amount of livestock ownership can be increased in order increasing the income.